Binomial Products are expressions which involve multiplying two term expressions by each other. USE FOIL METHOD.
If both binomial terms are the same
for example (2x+y)(2x+y) we may write it as (2x + y)2
We may remember the formula for these expressions as:
(a + b)2 = a2 + 2ab + b2
(a−b)2 = a2 −2ab + b2
We can now simplify an example such as
(2x + 2y)2 + (x−2y)2 = 4x2 + 8xy + 4y2 + x2 −4xy + 4y2
= 5x2 + 4xy + 8y2
Sum Times The Difference
We should notice that when we expand an expression such as (3x+2y)(3x−2y) we get a special result.
(3x + 2y)(3x−2y) = 9x2 −6xy + 6xy−4y2
= 9x2 −4y
So We Have A Special Rule
(a+b) (a-b) = a2 - b2